A parameterized model for the real-time reconstruction of underwater sound speed fields in oceanic eddy environment - Xu, Luochuan; Zhang, Anmin; Sun, Xuehai; Xu, Jian; Liu, Yi; Chen, Dan; Chen, Linglong (Frontiers in Marine Science, 2025)
Predicting underwater acoustic propagation is essential in marine acoustic operations, could be significantly affected by oceanic physical phenomena. In this paper, we focus on modeling the impact of oceanic eddies on underwater sound speed fields. We leverage the advantages of satellite remote sensing technology and Argo float data, proposing a parameterized model that considers environmental factors for the real-time reconstruction of underwater sound speed fields during eddy occurrences. The novel model distinguishes between the structures of eddies, categorizing them into eddy regions and environmental regions, thereby effectively preserving the acoustic characteristics of the eddies while accounting for the influence of the surrounding ocean environment on their internal structure. Unlike numerical simulations and in situ observational experiments, our parameterized model only requires surface characteristics of the eddies as input, enabling underwater sound speed field reconstruction to be completed within seconds and significantly enhancing reconstruction efficiency. Moreover, compared to the most commonly used acoustic field reconstruction methods, the proposed model achieves a 6.7% improvement in the accuracy of underwater sound speed reconstruction and a 13.5% improvement in the accuracy of acoustic propagation loss calculations. With its remarkable advantages in both reconstruction efficiency and accuracy, this model shows great potential for practical applications in marine acoustic operations.